Application Of Electronic Evidence As Extension Of Legal Civil Evidence Divorce Cases In Indonesia - Sukmasari, Ameilia; Frederik, Wulanmas; Kalalo, Merry Elisabeth; Soepeno, Muhammad Herro (Scholar Center, 2024)
Electronic evidence serves as a crucial component in civil trials, such as divorce cases, offering comprehensive proof to sway judges and ensure justice and legal certainty for involved parties. Nonetheless, disagreement persists regarding its classification, whether as supplementary or primary evidence, posing significant questions within formal and material law. This study employs normative juridical legal research, which scrutinizes theories, concepts, legal principles, and statutory regulations pertinent to the subject. Under Article 5(1) of the ITE Law, electronic evidence, including electronic information, documents, and their printouts, is recognized as valid legal evidence, extending the scope of admissible evidence in Indonesia. Formal requirements for electronic evidence, or digital evidence, need not be in written form; printouts are considered presumptive or preliminary evidence. However, material requirements stipulate that digital evidence must guarantee authenticity, integrity, and availability, often necessitating testimony from digital forensic experts. This dual nature of electronic evidence highlights its importance and complexity in contemporary legal proceedings, demanding a nuanced understanding and application within the framework of Indonesian law.